Fate of Warm Pacific Water in the Arctic Basin - Lin, Peigen; Pickart, Robert S.; Våge, Kjetil; Li, Jianqiang (Geophysical Research Letters, 2021)
Pacific Summer Water (PSW) plays a critical role in the ecosystem of the western Arctic Ocean, impacting sea-ice melt and providing freshwater to the basin. Most of the water exits the Chukchi Sea shelf through Barrow Canyon, but the manner in which this occurs and the ultimate fate of the water remain uncertain. Using an extensive collection of historical hydrographic and velocity data, we demonstrate how the PSW outflow depends on different wind conditions, dictating whether the warm water progresses eastward or westward away from the canyon. The current carrying the water westward along the continental slope splits into different branches, influenced by the strength and extent of the Beaufort Gyre, while the eastward penetration of PSW along the shelfbreak is limited. Our results provide the first broad-scale view of how PSW is transferred from the shelf to the basin, highlighting the role of winds, boundary currents, and eddy exchange. publishedVersion